Innovation in Tradition: Exploring Banyuwangi's Smart Village as a Cultural City Brand - Adelia Oktarina; Syamsi Mawardi; Cita Pertiwi; Nur Fitriana; Rabiatul Adwiyah (Kedeputian Bidang Ilmu Sosial dan Kemanusiaan (IPSK-LIPI), 2023)
Smart Kampung Banyuwangi is a Banyuwangi Regency government program that is supported by the government in realizing digitalization in the government sector. Even though it focuses on government digitalization, Smart Kampung Banyuwangi also attracts and has an impact on various aspects of community life and government in Banyuwangi, one of which is a form of city branding. This study aims to identify the use of government digital technology (digitalization) developed by Banyuwangi as a form of branding for Banyuwangi Regency. This paper uses a descriptive qualitative approach with a single holistic case study method with data sourced from literature reviews, observations, and field discussions. The results of the analysis show that digitalization carried out by the Government of Banyuwangi with the Smart Kampung Banyuwangi tagline not only encourages improving the quality of government systems and administration, but also encourages the implementation of community empowerment and improving the quality of internet infrastructure in Banyuwangi. Furthermore, the Smart Kampung Banyuwangi tagline can be used as a form of city branding that distinguishes Banyuwangi from other districts/cities in Indonesia. With this differentiating value, it is expected to be able to bring added value that supports regional development and increases people's welfare.